Optimum smoking time and temperature for frankfurters - Yu, Helen Sy (1968)
Two smoking processes of frankfurters were compared according to color, flavor, texture, microbial flora and over-all acceptability. Treatment A involved smoking at a higher temperature range for a shorter time, while Treatment B involved smoking at an initially lower temperature for a longer time. Microbiological and moisture changes that occurred during smoking were also studied and compared. The critical temperature for color change during smoking was between 130 and 140 °F. Heating beyond this temperature did not significantly increase color intensity. Color stability was related to the length of smoking, longer smoking resulted in a more stable color. Variations in smoking time and temperature did not affect significantly the flavor, texture and over-all acceptability of the final products. Although changes in microbial flora were more rapid in Treatment A, bacterial count of the final products were the same. Treatment B, with a modified longer finishing time, gave the best results considering all characteristics. The initial low temperature and long smoking time provided for maximum color development and stability.